Standardized Postmortem Forensic Examination Form - polat, Mustafa Önder; Meriç, Çağdaş; Altun, Gürcan (The Bulletin of Legal Medicine, 2021)
Objective: For the investigation of unnatural deaths all findings such as signs of injury, time and cause of death must be detected during the examination of the body. It is known that these examinations, which must be primarily carried out by forensic medicine specialists, are also carried out by general practitioners. In this study, it was aimed to build up a standardized form to give guidance to the physicians attending the postmortem examinations.Material and method: While creating the postmortem forensic examination form, the general forensic examination report form used in the field was taken as an example. The form was constructed with the sections of identification, postmortem findings, injury related lesions, and determination of the cause of death. Body diagrams to mark the lesions are also added.Discussion: It is known that a certain standardization is provided by the general forensic examination report forms in forensic cases. However, there is no such standardized form being used in our country. As the time interval prolonged between postmortem examination and autopsy, postmortem findings may change. For this reason, the findings during the postmortem examination must be defined and recorded in complete accuracy. Any deficiency or inaccuracy happened in this process could impede the course of justice. It is anticipated that by the usage of the form prepared for the requirements of physicians who carry out the postmortem examination, deficiencies in the practice can be reduced.